PEMBUATAN PERANGKAT LUNAK UNTUK MENDUKUNG PENGENDALIAN BANJIR DAS BENGAWAN SOLO HULU - WIJAYA, ADIEL PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
One of the flood control efforts on the upstream of Bengawan Solo River Basin is river flow setting through the spillway of Wonogiri Reservoir. The basic principle of reservoir operation for flood control purposes through the reservoir spillway discharge is setting the release discharge to the downstream so that does not happen overtopping dam and avoid the potential downstream inundation. Therefore, the performance of the reservoir operation in the flood period is dependent ability to estimate reservoir inflow flood hydrograph, fluctuations in water reservoir so as not to exceed the allowable critical elevation, and evaluation of flow conditions in prone areas in the downstream reservoir. It required an appropriate technology as a guide Wonogiri Reservoir operation during the flood period as a flood control measures that can evaluate the performance and the impact that may occur quickly. In this study has developed software that consists of three components, that is flood forecasting to estimate reservoir inflow flood hydrograph, reservoir flood routing for the evaluation of reservoir water level fluctuations not to exceed the allowable critical elevation, and hydrologic routing channels for the evaluation of the flow condition and water level in the downstream area. The third component of the model is integrated with hydrologic - hydraulic monitoring system data into a software package that is compiled using Microsoft Visual Studio Express 2012 and Microsoft Access. Application of hydrologic - hydraulic models developed in this study provides two basic information, which is the estimated inflow flood hydrograph of Wonogiri reservoir and the impact on the flow conditions in the downstream reservoir to AWLR Jurug in Surakarta to an operating arrangement scenario of spillway in flood period. With the support of the software, the Wonogiri Reservoir authority can obtain more information and more precise as the basis for determining the optimal decision in order to control flooding in the Upper Bengawan Solo Watershed. Keywords: Wonogiri Reservoir, flood forecasting, reservoir flood routing, hydrologic channel routing, optimal decision